PENGARUH PENDAPATAN PERKAPITA DAN IHK TERHADAP KONSUMSI MASYARAKAT DI KOTA BANJARMASIN - NOVI ZULISTRI ANJUNG SARI (PPJP Universitas Lambung Mangkurat, 2018)
This research is conducted (1) To know how the effect of per capita income on public consumption in Banjarmasin ; (2) To know how CPI to public consumption In Banjarmasin.This researchh was conducted to measure the variables that influence the consumption pattern of society by using macro economic concept. Economic variables that investigated are income Per Capita and CPI from 2000-2016 by using multiple linear regression analysis.Based on hypothesis testing it can be seen that the influence of income of CPI consumption in the city of Banjarmasin positively and significantly influence public consumption expenditure. Keywords: Income, CPI, Consumption